Analysis Of The Structure Of The Published Outputs In The Area Of Marketing Ethics - Hrehová, Daniela; Žiaran, Pavel (Communication Today, 2025)
Considering that marketing ethics is an interdisciplinary area includeing wide spectrum from marketing, management, ﬁnance and accountancy to philosophy, politics and law it requires general knowledge both of the students and academicians. Marketing ethics provides innumerable amount of the materials and topics for open discussion as well as for application in practice. Aims: Monitoring of academic journals in the area of marketing ethics tuition accessible in electronic databases by means of Centre for scientiﬁc-technical information SR portal. Procedure: (1) We focussed our attention on the content of monitored scientiﬁc and scholarly publications, which are of double character. (2) We paid attention to positive and negative attitudes towards marketing ethics education from the point of view of signiﬁcant academicians and experts. (3) We summarised the most important literary sources in the marketing ethics area (a) we investigated scientiﬁc sources in the area of entrepreneurially ethics tuition in general as well as the position, which is represented by the area of marketing ethics; (b) we analysed its content and its structure in academic journals in the speciﬁc area of marketing ethics tuition. Methodological and ideological basis for our survey was the publication „Half a Century of Marketing Ethics: Shifting Perspectives and Emerging Trends” by the authors Schlegelmilcha and Obersedeera. We had the goal to ﬁnd an optimal result, i.e. the articles dealing with the area of marketing ethics tuition, we tested various combinations of logical information retrieval items for each journal individually and database EBSCO, ProQuest, Web of Science, Google Scholar, ABI/Inform, Business Source Premier. From the journal review we suggested six categories: measurement of ethical values and attitudes; particular pedagogical methods; proposal and structure of ethics course; measurement of education efﬁciency, ethics integration on the Faculty level; ethical codices and norms, (1) in order to be highly consistent and relevant for categorization of the journals, (2) to enable to monitor academic knowledge and research trends in this area in clear and comprehensible way. We have elaborated in the survey our own “local” impact factor for the specific area of marketing ethies education and tuition. Results: Discussions of academicians, specialists and students about marketing ethics and ethical issues are useful and important. Students need preparation, mentoring and counselling while solving ethical problems, which occur during marketing ethics tuition in the academic ﬁeld, but also in practice. Academic and scientiﬁc sources in the area of marketing ethics education are an excellent “instruction”. In the centre of academic interest in the area of marketing ethics there are topics about academic methods and measurements of ethical values and attitudes related above all with marketing education. Marketing ethics should include tuition of one or several topics: marketing principles, marketing management, strategic marketing, marketing research, digital/ new media of marketing, marketing of services and trade marking.